Skin Coverage for Acute Fingertip Injuries – A case series of Traumatic Injury at Prof. Dr. R. Soeharso Hospital, Surakarta - Sumarwoto, Tito; Hadinoto, Seti Aji; Bayudono, Sigit; Utomo, Pamudji (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Traumatic fingertip injuries are the most common injuries of the hand. Several million estimated visits to primary care providers and the emergency department occur each year. But the handling is often not done properly and comprehensively. Reconstruction of the fingertip must be done as soon as possible in the acute stage, resulting in better outcomes in the future. Aim of the surgery was to restore as much finger length, preserve sensation fingertip properties and achieve normal nail growth, and cosmetics appearance as well.Case presentation: Three cases of emergency patients with fingertip injury treated at the hospital in the acute setting. All of these patients experienced work injuries and were immediately taken to the emergency department.Results: The debridement and skin coverage reconstruction were carried out. Functional and aesthetic outcome were a postoperative assessment.Conclusion: The right choice of treatment and good wound care will produce a better outcome.Keywords: traumatic injury, fingertip injury, skin coverageCorrespondence: Tito Sumarwoto. Department of Orthopaedic and Traumatology, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java.Indonesian Journal of Medicine (2020), 05(04): 331-336https://doi.org/10.26911/theijmed.2020.05.04.08.